The Influence Of Sales Promotion, Financial Literacy, Hedonic Browsing And Utilitarian Browsing On Impulse Buying (Case Study Of Shopee Users On Gen Z In West Java) - Kurnia, Najwan Fakhrin; firmialy, sita deliyana (UNIVERSITAS PAKUAN, 2024)
The widespread development of the internet network today has created new trends and lifestyles in society, indirectly triggering impulse buying behavior. Several factors influencing this behavior involve sales promotion, financial literacy, hedonic browsing, and utilitarian browsing. Shopee, as one of the leading e-commerce platforms in Indonesia, has captured the attention of Generation Z, achieving a market share of 69.9%. West Java leads in the number of users and e-commerce transactions nationally. The aim of this research is to assess the impact of sales promotion, financial literacy, hedonic browsing, and utilitarian browsing on the tendency of impulse buying among Generation Z Shopee users in West Java. Using a quantitative approach and collecting data through Likert scale questionnaires, a sample of 100 Generation Z respondents who are e-commerce users in West Java was taken. Analysis using SmartPLS software indicates that sales promotion and hedonic browsing have a significant impact on impulse buying, while financial literacy and utilitarian browsing do not significantly influence impulse buying behavior.